Fluorescence properties of yellow light emitting carbon quantum dots and their application for effective recognition of heavy metal ions in aqueous medium. Issue 12 (8th May 2021) - Raj, Savan K.; Rathod, Nehal H.; Tripathi, Balram; Patidar, Rajesh; Kulshrestha, Vaibhav
Abstract: Water‐dispersible and fluorescence‐stable carbon quantum dots (CQDs) have been synthesized at gram scale using pyrene as carbon precursor by employing the bottom‐up approach. X‐ray diffraction, FTIR, Raman spectroscopy and UV visible spectroscopy confirm the formation of CQDs. TEM images shows that size of the CQDs ranges from 2 to 5 nm. A detailed study of their optical and fluorescence characteristics was performed. Their aqueous dispersion radiates bright yellow light under UV lamp (365 nm). The research work includes derivation of their excitation wavelength, observation of influence of dilution on fluorescence and monitoring of emission intensity for about 4 months. The CQDs can effectively recognize the presence of heavy metal ions in aqueous medium at neutral pH via fluorescence quenching. Abstract : Carbon quantum dots (CQDs) synthesized at gram scale using low‐cost material. A detailed study of fluorescence characteristics of yellow light emitting CQDs is done. These dots are fluorescence‐stable for about 4 months. These have been utilized for effective recognition of Fe 3+, Cu 2+, and Cr 3+ ions in aqueous medium.